The Role of Fintech in SME Financing: A Bibliometric Review - Muchamad Rizky Fauzi; Puji Handayati; Ely Siswanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The rapid growth of financial technology (fintech) has significantly transformed the funding landscape for Small and Medium Enterprises (SMEs), offering innovative financial solutions beyond traditional banking institutions. This study presents a bibliometric analysis of fintech’s role in SME financing, identifying emerging trends and research gaps. Utilizing bibliographic coupling and co-occurrence network analysis, data from Scopus were analyzed to uncover the intellectual structure and evolution of research in this field. The results highlight key themes, including the integration of blockchain, peer-to-peer lending, financial inclusion, and crowdfunding in SME financing. A particular focus on Islamic finance and Islamic crowdfunding indicates a growing interest in alternative financing mechanisms that align with Sharia principles. Additionally, the study reveals an increasing academic focus on fintech adoption in developing economies, particularly in Indonesia and Nigeria, where access to capital remains a critical challenge. The findings underscore fintech’s role in democratizing financial access for SMEs, bridging funding gaps, and fostering economic growth. Future research should investigate regulatory frameworks, risk management strategies, and technological adoption models to optimize the impact of fintech on sustainability in SME financing.